PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (Studi pada Perusahaan Sektor Pertambangan di BEI Periode 2010 – 2016) - Susanty, Dessy; Bastian, Elvin (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
Important information for investors to make investment decisions reflected in the financial statements. Investors must expect a high rate of return on the funds invested into the company. This study aimed to analyze the influence of Return On Asset, Debt to Equity Ratio, Current Ratio, Price To Book Value and Firm Size on stock returns. Objects of research are amining companies listed on the Indonesia Stock Exchange during 7 year period 2010 to 2016 have been selected as sample.. Data used to analysis is the financial statements (Balance Sheet and Income Statement), using the technique of multiple regression analysis and ratios, criteria through the purposive sampling method. The data processed by using SPSS program version 20.0. It was concluded from the results of data analysis that : variable Debt to Equity Ratio, Price To Book Value and Firm Size have been significant influenceto to the stock return. Return On Asset and Current Ratio no effect on stock return.Keywords: Return On Asset, Debt to Equity Ratio, Current Ratio, Price to Book Value, Firm Size, Stock Return.